2012
DOI: 10.1002/ffj.3096
|View full text |Cite
|
Sign up to set email alerts
|

Temporal development of sesquiterpene hydrocarbon profiles of different grape varieties during ripening

Abstract: To investigate the profiles of sesquiterpene hydrocarbons in grape berries at different developmental stages several cultivars of Vitis vinifera (Gewürztraminer, Riesling, Yellow Muscat, Shiraz, Lemberger, Cabernet Sauvignon) were analysed during ripening. Therefore, HS‐SPME‐GC‐MS measurements were performed with intact grape berries. The measurements demonstrated that grapes emit numerous sesquiterpene hydrocarbons and that the sesquiterpene profile exhibits a characteristic profile, depending on the variety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 26 publications
2
31
0
Order By: Relevance
“…Sesquiterpenes are synthesized via the mevalonate (MVA) pathway localized in the cytosol and the remarkable diversity of sesquiterpenes is generated by the large family of sesquiterpene synthases (TPS-a), recently discovered in grapes, each producing multiple substrates [29]. Further research demonstrated that grapes produce numerous sesquiterpene hydrocarbons with a characteristic profile depending on the variety and the developmental stage [30].…”
Section: Resultsmentioning
confidence: 99%
“…Sesquiterpenes are synthesized via the mevalonate (MVA) pathway localized in the cytosol and the remarkable diversity of sesquiterpenes is generated by the large family of sesquiterpene synthases (TPS-a), recently discovered in grapes, each producing multiple substrates [29]. Further research demonstrated that grapes produce numerous sesquiterpene hydrocarbons with a characteristic profile depending on the variety and the developmental stage [30].…”
Section: Resultsmentioning
confidence: 99%
“…Rotundone concentration in musts and wines may depend on several factors such as cultivar, region, and mesoclimate; in particular, low temperatures may result in increased rotundone accumulation [17], and in effect, it was not been identified in Syrah samples from Mediterranean area [23].…”
Section: Discussionmentioning
confidence: 98%
“…As regards Syrah wine volatiles, information is reported in literature on Australian wines from vines cultivated in cool and warm climate grape-growing regions and mainly on the key aroma compounds responsible for the peppery notes [15][16][17][18][19].…”
mentioning
confidence: 99%
“…SBSE-PDMS has a stationary phase volume much more higher respect to SPME-PDMS: the maximum volume of PDMS in a SPME fiber is 0.5 microliter (film thickness of 100 micrometer) whereas PDMS in SBSE can provide from 24 to 126 microliters of volume. Thus, the sensitivity of PDMS-SBSE is higher, resulting in a higher volatile extraction respect to SPME and in the detection and identification of compounds present at very low concentrations, such as sesquiterpenes (May & Wüst, 2012;Ferrandino, Carlomagno, Baldassarre & Schubert, 2012) or malodors in wastewaters (Loughrin, 2006). PDMS stir bars were also used for the detection of stilbene molecules in wines (Cacho, Campillo, Viñas & Hernández-Córdoba, 2013).…”
Section: Introductionmentioning
confidence: 98%